Jewish students in Strzygowski’s Vienna Institute and the study of Jewish art: a forgotten chapter in the history of the Vienna School - Michael Young (Journal of Art Historiography, 2023)
Josef Strzygowski, inscribed in the annals of art history as a racialist and an anti-semite, had many devoted Jewish students. Strzygowski cast a long shadow over many of the earliest specimens of Jewish art history in Vienna. In an unpublished article written in English, and in the Beurteilungen of the Jewish-themed dissertations he supervised, Strzygowski stressed the importance of Jewish art historians studying Jewish art. The forgotten, mostly unpublished efforts of these Jewish art historians working on Jewish topics form a counterpart to the better-known contemporary works of Jewish art history produced in Berlin. This study examines the work of four Jewish doctorandi of Strzygowski, Max Eisler, Otto Schneid, Paul Koeser and Friedricke Nobl-Stern and considers the interplay between anti-semitism, Zionism and entrenched beliefs in the connection between ethnicity or nationality and art during a fateful period for Vienna and for the Jews of Europe.